Evaluation of analgesic activity of ethanol and ethyl acetate extracts from basil leaves (Ocimum x africanum L.) in acetic acid-induced rat models - Sarimanah, Uvit; Nofita; Angin, Martianus Perangin (Pharmacy Reports, 2023)
Analgesics are medications that alleviate pain without impairing consciousness, with certain plants, such as basil (Ocimum x africanum L.), showing potential as natural pain relievers. This research investigated the analgesic effects of ethanol and ethyl acetate extracts from basil leaves on acetic acid-induced pain in rats. The study utilized percolation extraction methods with 96% ethanol and ethyl acetate solvents. Twenty-eight male white rats were divided into seven groups: one normal control group without treatment or induction, one negative control group receiving 0.5% CMC-Na, two groups treated with ethanol extracts of basil leaves at doses of 400 mg/kg BW and 800 mg/kg BW, two groups treated with ethyl acetate extracts at the same doses, and one positive control group administered 50 mg/kg BW diclofenac sodium. Thirty minutes post-treatment, 1% acetic acid was injected intraperitoneally, and writhing responses were observed over 60 minutes. The data on percentage protection from writhing were analyzed using One-way ANOVA followed by the LSD test. The findings revealed that both the ethanol and ethyl acetate extracts at an 800 mg/kg BW dosage closely matched the analgesic effectiveness of the diclofenac sodium group.